Enhancing locomotor skills in preschoolers through play jump rope - Nancy Trisari Schiff; Andy Supriady (CV Rezki Media, 2026)
Background: Fundamental Motor Skills (FMS), particularly in the Locomotor Skills domain, are an essential prerequisite for lifelong physical participation. However, the dominance of a sedentary lifestyle threatens young children's mastery of these skills. Objectives: This study aims to test and prove the effectiveness of the jump rope play intervention program in improving locomotor skills in 5–6-year-old children. Methods: This research uses a quasi-experimental one-group pretest-posttest design. The sample consisted of 19 males and 11 females, for a total of 30 children. Locomotor skills are measured objectively using the Locomotor subtest of the Test of Gross Motor Development-2 (TGMD-2). The Jump Rope Game intervention was implemented in a structured manner over 8 weeks (3 sessions/week). The data were analyzed using the Paired-Samples T-Test. Results: The research results show a highly significant improvement in locomotor skills scores after the intervention. The average score increased from 23.30 on the pretest to 27.87 on the posttest, reflecting a 19.61% increase. The paired-samples t-test yielded a p-value of 0.000 (p<0.05), confirming that the difference between the two measurements was statistically significant. Conclusions: Jump rope games have proven to be an effective, efficient, and enjoyable intervention for significantly improving young children's locomotor skills. This research recommends integrating inexpensive, easily accessible play-based activities into the early childhood education curriculum as a practical strategy to support physical literacy and address basic movement deficits.